Exploring the Role of Brand Engagement in Meme Marketing Effectiveness - Siti Alhamra Salqaura; Nasib Nasib; Siti Sabrina Salqaura (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Social media development and the phenomenon of meme marketing have become increasingly viral. The shift from traditional advertising to community-based and participatory content, such as memes, has emerged as a trending notion in contemporary marketing. This shift has necessitated companies to become more innovative in capturing attention, engaging consumers, and fostering loyalty. This research aims to examine the relationship between virality meme marketing, brand personality, and consumer loyalty, with brand engagement acting as a mediator. This study employs a quantitative approach, utilizing PLS-SEM through SmartPLS 4.0 software, with a sample of 220 active respondents. The questionnaire was distributed online using Google Forms, and purposive sampling was applied. The findings indicate that virality meme marketing, and brand personality have a significant enhancing effect on brand engagement, which in turn mediates the effect on customer loyalty. However, a surprising finding emerged regarding the direct effect of virality meme marketing on customer loyalty, where virality meme marketing negatively and insignificantly influences customer loyalty.